2006
DOI: 10.1152/ajprenal.00052.2005
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction biology and kidney dysfunction

Abstract: The epithelial tight junction (TJ) has three major functions. As a "gate," it serves as a regulatory barrier separating and maintaining biological fluid compartments of different composition. As a "fence," it generates and maintains the apicobasal polarity of cells that form the confluent epithelium. Finally, the TJ proteins form a trafficking and signaling platform that regulates cell growth, proliferation, differentiation, and dedifferentiation. Six examples are selected that illustrate the emerging link bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
125
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(135 citation statements)
references
References 177 publications
0
125
0
5
Order By: Relevance
“…The disruption of tight junction is involved in several diseases, including gastrointestinal, lung and kidney diseases. 22,23 However, to the best of our knowledge, its association with kidney stone disease remains unknown.…”
mentioning
confidence: 99%
“…The disruption of tight junction is involved in several diseases, including gastrointestinal, lung and kidney diseases. 22,23 However, to the best of our knowledge, its association with kidney stone disease remains unknown.…”
mentioning
confidence: 99%
“…9,19 Following the observation that a naturally occurring knockout model in Japanese black cattle shows early-onset renal failure with diffuse interstitial nephritis, 20 it was recently speculated that claudin-16, like other claudins, may also be involved in the regulation of cell growth, proliferation, differentiation, and dedifferentiation. 21 Hou et al 22 described the functional analysis of claudin-16 in polarized cell lines. They demonstrated that in LLC-PK1 cells, claudin-16 modulated the ion selectivity of the TJ by selectively increasing the permeability of Na ϩ with no effects on Cl Ϫ , resulting in a high permeability ratio of Na ϩ to Cl Ϫ .…”
mentioning
confidence: 99%
“…Sodium and chloride are reabsorbed by either of two mechanisms: Electroneutral Na-Cl cotransport occurs via the thiazide-sensitive Na-Cl cotransporter (NCC) in the distal convoluted tubule and connecting tubule, and electrogenic Na ϩ reabsorption occurs via the epithelial Na ϩ channel ENaC in the connecting tubule and collecting duct (1). Electrogenic Na ϩ reabsorption provides the electrical driving force for either Cl Ϫ reabsorption via paracellular flux or, alternatively, for K ϩ secretion, which, under normal circumstances, occurs via the renal outer medullary K ϩ channel (ROMK) (2). The key roles of each of these mediators in normal volume, blood pressure, and electrolyte homeostasis is demonstrated by the consequences of mutations that result in increased or diminished activities of these gene products (3).…”
mentioning
confidence: 99%